Pengaruh Film Animasi Terhadap Perilaku Moral Anak Usia 5-6 Tahun - Nur Fajri Indayani; Rusmayadi Rusmayadi; Muhammad Akil Musi (JECED : Journal of Early Childhood Education and Development, 2022)
The moral behavior of children today is quite worrying, especially in early childhood. This can be triggered by several factors, one of which is watching animated films that are used to be consumed by children. This study aims to examine the relationship and impact between animated films (y) on children's moral behavior (x). The method in this research is correlational using bivariate analysis technique. The object of the research is group B students with a total sample of 12 children. From the results of data processing, the r value of 0.973 is obtained, the correlation coefficient of determination is 2.7% so that interpreting the relationship and influence between animated films and the moral behavior of students aged 5-6 years has a positive influence.